Analisis Sanksi Perpajakan Dan Pengetahuan Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Pada PT. SIP Inti Palapa Logistik - Oky Syahputra; Irma Herliza Rizki (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to determine the effect of Knowledge of Taxation Regulations and Tax Sanctions toward Taxpayer Compliance in PT. SIP Inti Palapa Logistik. The population in this study are employees in PT. SIP Inti Palapa Logistik. Samples taken as many as 50 respondents by using purposive sampling. Result of research partially indicate that Knowledge of Taxation Regulations has effect and significantly to Taxpayer Compliance in PT. SIP Inti Palapa Logistik.. Results of research partially indicate that Tax Sanctions has effect and significantly to Taxpayer Compliance in PT. SIP Inti Palapa Logistik. Results of simultaneously the Knowledge of Taxation Regulations and Tax Sanctions has effect and significantly to Taxpayer Compliance in PT. SIP Inti Palapa Logistik. The results of the coefficient of determination test show that the Taxpayer Compliance variable can be explained by the variables of Knowledge of Taxation Regulations and Tax Sanctions, while the remaining by other variables not examined in this study such as Tax Administration System, Tax Service Quality, Tax Audit Quality, Tax Rates and Taxpayer Behavior.